Linking Human Resource Management Practices with Employee Commitment - Sita Bhandari (Journal of Business and Social Sciences, 2025)
The research paper is aimed at studying the link between HRM practices and employee commitment in Nepalese businesses. The paper has employed descriptive research design and the correlational research design to establish the relationship between the HRM practices and employee commitment in the Nepalese business. Primary data was used as the primary source of information and it was collected through the assistance of the well-organized questionnaire created to respond to the objective of the research. The questionnaires will be mailed to 10 organizations representing both the service and manufacturing sectors in Nepal, and the questionnaires that will be sent will make 250 altogether with 25 questionnaires in each business. These gave rise to 155 respondents returning these questionnaires therefore a response rate of 62 percent. All its items will be measured on a five-point Likert scale in the survey. It may also be observed, in terms of the empirical information that all the regions of HRM practices have most positive correlation with all the regions associated with the employee commitment. The employees are morally obliged to stay within their organizations where they perceive the firms to have good HRM practices and processes. It is therefore desirable that effective HRM practices should be developed and implemented to encourage all forms of employees in a given organization. This has long-run benefits to the business in terms of realizing its targets.